Survey of Reactive Hyperplastic Lesions of the Oral Cavity in Mashhad, Northeast Iran - Maryam Amirchaghmaghi; Nooshin Mohtasham; Pegah Mosannen Mozafari; Zohreh Dalirsani (Tabriz University of Medical Sciences, 2011)
Background and aims. Reactive hyperplasias (RHs) are common oral mucosal lesions caused by irritation of the mucosa. The aim of this study was to evaluate the frequencies of various types of oral RHs in a university clinic. Materials and methods. Oral RH cases, undergone biopsy in a four-year period, were studied retrospectively. Data including age and gender as well as the location and clinical characteristics of the lesion were collected and analyzed. Results. A total of 123 cases (age range 7-79 years old; mean: 38.8 ± 18.50 years; male: female ratio, 1.9:1) were evaluated. Over a half of the lesions including pyogenic granuloma, giant cell granuloma, and peripheral ossifying fibroma were found in gingiva (52%). Fibroma involved mostly the buccal mucosa. Most lesions had smooth surface and sessile base. Conclusion. The clinical features of oral inflammatory hyperplasia in the studied sample were similar to those previously reported.